History And Moral Education In Nation Building: A Discourse On The Nigeria’s Broken Systems - Abdulrahman, Yusuf Maigida (Archives of Business Research, 2020)
Systems are fast collapsing in Nigeria, including education. The good old days of the country were devoid of all the negativities of today. Studies have shown that a number of forces and causes were responsible for where the country has come to find herself. However, to be historical is sine-qua-non to retracing our bearing and recognizing education as a potent instrument for a morally upright society. The connection between history and moral education was chronicled, with clear focus on the place of history and moral education from the retrospective standpoints; capturing colonial and post-colonial characteristics. Ugly state of affairs in Nigeria and ways of addressing the situations were highlighted, for nation building. Character training and promotion of right type of values recommended.